Finite element analysis of braced excavation with jet grouting - Lim, Eng Yang (Nanyang Technological University, 2021)
Braced excavations are becoming prevalent in an increasingly urbanised world. For excavation in soft clays, jet grout piles (JGP) are often used as a ground improvement technique to reduce the wall deflections and increase the factor of safety with respect to basal heave stability. This project studies and reports on the effects of jet grouted piles on the performance and behaviour of a typical deep braced excavation in soft clay.